Access to Long Term Care After a Wealth Shock: Evidence from The Housing Bubble and Burst - Joan Costa-i-Font; Richard G. Frank; Katherine Swartz (Center for Economic Studies and ifo Institute (CESifo), 2017)
Home equity is the primary self-funding mechanism for long term services and supports (LTSS). Using data from the relevant waves of the Health and Retirement Study (1996-2010), we exploit the exogenous variation in the form of wealth shocks resulting from the value of housing assets, to examine the effect of wealth on use of home health, unpaid help and nursing home care by older adults. We find a significant increase in the use of paid home health care and unpaid informal care but no effect on nursing home care access. We conduct a placebo test on individuals who do not own property; their use of LTSS was not affected by the housing wealth changes. The findings suggest that a wealth shock exerts a positive and significant effect on the uptake of home health and some effect on unpaid care but no significant effect on nursing home care.
Keywords: I18; J14; 330; long term care; housing equity; housing bubble; informal care; home health care; nursing home care